Uji Aktivitas Minyak Atsiri Daun Pala (Myristica fragrans Houtt.) Sebagai Antibakteri: Activity Test of Nutmeg Leaf Essential Oil (Myristica fragrans Houtt.) as Antibacterial - Halimathussadiah Halimathussadiah; Dewi Rahmawati; Niken Indriyanti (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Antibacterials are compounds that are useful in controlling bacterial growth that can harm humans and avoid pathogens that can be a source of disease for the body. Nutmeg essential oil (Myristica fragrans Houtt.) Is known to contain various compounds including flavonoids, alkaloids, phenols and terpenoids which can be used as antibacterial agents. The purpose of this study was to determine the activity of nutmeg essential oil as an antibacterial. The antibacterial test method uses the well diffusion method using a 6 mm buffer. Nutmeg essential oil is made in 4 concentration series, namely F1 (40%), F2 (60%), F3 (80%), F4 (100%), 10% DMSO control. The data analysis method is a descriptive method in the form of data that is presented in the form of tables and figures. The results of the antibacterial activity test showed that the essential oil of nutmeg leaves had antibacterial activity against Escherchia coli, Staphylococcus aureus, Vibrio cholerae, Pseudomonas aeruginosa, Bacillus subtilis, and Staphylococcus epidermidis in the best concentrations, namely 100% respectively of 6.79mm ? 0.67; 5.56mm ? 0.18; 6.75mm ? 0.82; 14.61mm ? 1.10; 17.03 mm ? 3.90; 5.39mm ? 0.75; control there is no antibacterial activity. The response of each bacteria was medium-strong and the best concentration was taken from the highest concentration because the higher the essential oil concentration of nutmeg leaves, the greater the bacterial inhibitory activity.